Effect of maturation and cold storage on the organic acid composition of myrtle fruits. (16th May 2012) - Mulas, Maurizio; Fadda, Angela; Angioni, Alberto
Abstract BACKGROUND: The effect of maturation and senescence on the chemical composition of two myrtle cultivars was studied in mature, overripe and cold‐stored fruits in order to find the most appropriate harvesting period and best storage technology for industrial purposes. RESULTS: After cold storage at 10 °C for 15 days, berry weight loss ranged from 12.5 to 18.4%, with the highest losses in less mature fruits. Titratable acidity decreased during maturation and cold storage in both cultivars. Reducing and total sugars increased during maturation. Anthocyanin concentration increased during maturation but decreased in overripe berries. The major organic acids in myrtle fruits were quinic, malic and gluconic acids. In fresh and cold‐stored fruits, malic acid rose to 3 g kg−1 and decreased thereafter. Quinic acid peaked at 90 or 120 days after bloom and decreased thereafter to reach low concentrations in mature fruits. CONCLUSION: Cold storage for 15 days at 10 °C does not affect myrtle fruit quality for liqueur production. Anthocyanin concentration is the best indicator of harvest time for industrial purposes. Gluconic acid concentration is high in mature, overripe and cold‐stored berries. This parameter can be used as a marker of the onset of fruit senescence. Copyright © 2012 Society of Chemical Industry